2005
DOI: 10.1021/jp0537815
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characterization of Polyelectrolyte/Gold Nanoparticle Multilayers Self-Assembled on Gold Electrodes

Abstract: Polyelectrolyte/gold nanoparticle multilayers composed of poly(L-lysine) (pLys) and mercaptosuccinic acid (MSA) stabilized gold nanoparticles (Au NPs) were built up using the electrostatic layer-by-layer self-assembly technique upon a gold electrode modified with a first layer of MSA. The assemblies were characterized using UV-vis absorption spectroscopy, cyclic and square-wave voltammetry, electrochemical impedance spectroscopy, and atomic force microscopy. Charge transport through the multilayer was studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
128
3
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(147 citation statements)
references
References 52 publications
(170 reference statements)
10
128
3
6
Order By: Relevance
“…Moreover, the overall electrochemical process is strongly dependent of the nature of the outermost layer. This dependence of the electrochemical process on the nature of the outermost layer has been observed for the first time at mercaptosuccinic stabilized gold nanoparticle (Au-MSA)/poly-Lysine multilayers self-assembled on gold electrodes (Chirea et al, 2005). The difference between these two types of multilayers is in the nature of the interaction between the redox probes in solution and the outermost layers.…”
Section: Electrochemical Characterization Of Multilayers Containing Smentioning
confidence: 84%
See 3 more Smart Citations
“…Moreover, the overall electrochemical process is strongly dependent of the nature of the outermost layer. This dependence of the electrochemical process on the nature of the outermost layer has been observed for the first time at mercaptosuccinic stabilized gold nanoparticle (Au-MSA)/poly-Lysine multilayers self-assembled on gold electrodes (Chirea et al, 2005). The difference between these two types of multilayers is in the nature of the interaction between the redox probes in solution and the outermost layers.…”
Section: Electrochemical Characterization Of Multilayers Containing Smentioning
confidence: 84%
“…In our previous work (Chirea et al, 2005), the depressed semicircles observed in the EIS spectra were due to a repelling effect (electrostatic repulsion ) between the outermost layers of negatively charged gold nanoparticles (Au-MSA NPs) and negatively charge redox probes ([Fe(CN) 6 ] 3-/4-) in solution. It has to be mentioned also that the electron transfer was mediated by the Au-MSA NPs when they were covered by a positively charged poly-Lysine layer which facilitated the diffusion of the electroactive species through the film based on electrostatic attraction.…”
Section: Electrochemical Characterization Of Multilayers Containing Smentioning
confidence: 94%
See 2 more Smart Citations
“…EIS has been one of the primary techniques to characterize the electronic communication of the analyte with the modified electrodes. [36][37][38][39][40][41] Recently, Calvo et al demonstrated the use of EIS in measuring ionic diffusion coefficients in pyridine derivatized (PAH│PSS) multilayer films. 42 Other advances also include EIS studies for explaining catalytic and charge storage efficiencies of LbL assembled nano-scale species such as gold, [43][44][45] titanium dioxide, 46 vanadium pentoxide, 40 polyoxometalates, 47 and carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%